Du capsien chasseur au capsien pasteur : pour un modèle régional de néolithisation - Belhouchet, Lotfi (Archaeology of the Maghreb, 2022)
Studies on the Capsian culture have been considerably enriched in recent years, but have not yet been properly synthesised to establish the current state of research. This volume draws on recent fieldwork to put forward a model for neolithisation in the Eastern Maghreb.